Quality system as a mediating variable of the relationship between lean manufacturing and operational performance in the food industry - Budianto Budianto; Zefki Okta Feri; Qomarotun Nurlaila; Helena Sitorus; Tina Hernawati Suryatman (SINERGI, 2023)
The failure to implement lean manufacturing (LM) in the food industry was caused by the overlapping application of LM tools. The application of LM in the food industry is experiencing problems in the form of confusion in the placement of QS or Quality Control (QC). This problem is the background of this research. The objective of this study is to compare two methods of the implementation of LM in improving operational performance (OP), namely (1) making quality control (QC) a part of LM practice and (2) making quality control (QC) a part of the quality system (QS). The applied analytical method was the Structural Equation Modelling (SEM) based on Partial Least Square (PLS). The research findings indicated that "making QC a part of QS" can optimally mediate increasing LM against OP. This study's originality is a comparison of the relationship between LM and OP based on the two methods with large sample sizes. The implications of the findings are expected to become recommendations for applying LM in the food industry, especially in terms of placing quality in its implementation.